Chronic Hyperglycemia Compromises Mitochondrial Function in Corneal Epithelial Cells: Implications for the Diabetic Cornea - Natalia Mussi; Whitney L. Stuard; Jose Marcos Sanches; Danielle M. Robertson (Cells, 2022)
Mitochondrial dysfunction is a major pathophysiological event leading to the onset of diabetic complications. This study investigated the temporal effects of hyperglycemia on mitochondrial metabolism in corneal epithelial cells. To accomplish this, human telomerase-immortalized corneal epithelial cells were cultured in a defined growth medium containing 6 mM glucose. To simulate hyperglycemia, cells were cultured in a medium containing 25 mM D-glucose, and control cells were cultured in mannitol. Using metabolic flux analysis, there was a hyperosmolar-mediated increase in mitochondrial respiration after 24 h. By day 5, there was a decrease in spare respiratory capacity in cells subject to high glucose that remained suppressed throughout the 14-day period. Although respiration remained high through day 9, glycolysis was decreased. Mitochondrial respiration was decreased by day 14. This was accompanied by the restoration of glycolysis to normoglycemic levels. These changes paralleled a decrease in mitochondrial polarization and cell cycle arrest. Together, these data show that chronic but not acute hyperglycemic stress leads to mitochondrial dysfunction. Moreover, the hyperglycemia-induced loss of spare respiratory capacity reduces the ability of corneal epithelial cells to respond to subsequent stress. Compromised mitochondrial function represents a previously unexplored mechanism that likely contributes to corneal complications in diabetes.